Prevalence of High Blood Pressure and its Relationship with Body Weight Factors among Inpatients with Schizophrenia in Taiwan - Yu-Li Lan, PhD; Tzy-Ling Chen, PhD (Elsevier, 2012)
Purpose: The objective of this study was to document the prevalence of high blood pressure (BP) and to explore its relationship with weight among inpatients with schizophrenia. Additionally, other possible risk factors impacting BP levels in relation to patients' demographic characteristics and use of atypical antipsychotic drugs and medications to reduce blood pressure were analyzed. Methods: Using medical records, demographic data, and results of physical examination, this cross-sectional study investigated the prevalence of hypertension and high BP and its association with body weight among 1,030 inpatients with schizophrenia in a large psychiatric facility in Taiwan. Results: The prevalence of high BP and hypertension were found to be higher among inpatients with schizophrenia in Taiwan in comparison with those of the general population in line with the latest evidence. Hypertension was significantly associated with body mass index; meanwhile, other risk factors, including age, gender, length of hospital stay, time since initial schizophrenia diagnosis, medications used to reduce blood pressure, and atypical antipsychotics, were identified. However, body mass index was the most effective predictor of blood pressure in the study. Conclusion: The findings of this research shed light on the importance of developing effective weight and blood pressure monitoring and management programs for inpatients with schizophrenia. There is also a need for clinical nurses to employ multiple behavioral intervention strategies to minimize risks of high BP in patients with schizophrenia. We recommend that clinical nurses carefully monitor and control BP among inpatients with schizophrenia.